Critical environmental education and interdisciplinary projects: A study of high school students’ productions (Revista Contexto & Educação, 2026)
This article presents the implementation of an Interdisciplinary Didactic Sequence (IDS), based on Critical Environmental Education (CEE) and Interdisciplinary Project-Based Learning (IPBL), with the theme "Sustainable Consumption and Production". The objective was to investigate how students articulate theory, memories of everyday experiences, and socio-environmental sensitivities during the projects, focusing on a critical understanding of socio-environmental challenges. The research was developed with 27 students from the 2nd year of high school at a public school in Paraná, through participant observation and qualitative analysis of student productions. Content analysis revealed the predominance of the Critical Perspective of Environmental Education, followed by the Conservationist/Resource-Based Perspective in the productions, as well as that 82% of the students demonstrated high engagement in the activities. The development of the projects favored the articulation between theory and practice, as well as the production of student narratives about the environment, mobilizing memories and sensitivities. It is concluded that the integration between CEE and IPBL constitutes a positive strategy for the formation of critical, participatory citizens who are sensitive to socio-environmental injustices.
Keywords: Interdisciplinary teaching sequence; sustainable consumption; project-based learning